The importance of actual use in defining and measuring innovative behaviour: Comparison of e-book reader users and non-users - Waheed, Mehwish; Klobas, Jane E.; Kaur, Kiran (SAGE Publications, 2017)
This study introduces the concept of personal innovative behaviour and demonstrates its validity in the context of e-book reader adoption and use. Personal innovative behaviour, unlike measures of consumer innovativeness, amalgamates decisions about product adoption with reports of the product’s actual use. Quantitative methodology was used, and probability proportional stratified sampling technique was used to obtain the proportionate sample. Items to measure personal innovative behaviour for e-book readers were included in a questionnaire distributed to students at a Malaysian university. Of the 386 participants, 79% used the e-book reader, half of them for academic purposes. Confirmatory factor analysis using Amos tested the concept of personal innovative behaviour for both users and non-users. The results indicated that the underlying dimensions, (intended Adoption Behaviour and actual Use Behaviour), could be measured and combined in a structural model only for users, i.e. innovators. Good model fit confirmed the validity and reliability of the framework. The redefined construct and scale validation will be helpful to researchers to measure the individual personal behaviour in terms of their final decision to adopt and actual usage of the novel product. The personal innovative behaviour scale presented here can be used by researchers and practitioners to measure adoption and use of personal information products and devices. The two dimensional conceptualization of personal innovative behaviour (intended Adoption Behaviour and actual Use Behaviour) reconciles similarities and differences between the decision and action variables in innovation diffusion theory and the technology acceptance model.